Profile of Vitamin D Levels Among Elderly Women with Knee Osteoarthritis in South Tangerang - Wipan Kurniawan; Achmad Zaki; Mery Nitalia; Bisatyo Mardjikoen; Hiro Putra Faisal; Melia Fatrani Rufaidah (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: The number of older people over 60 in Indonesia has doubled in the last five decades (1971-2020). Knee osteoarthritis is one of the non-communicable diseases arising in the elderly population. One of the risk factors known is low levels of vitamin D. This study aims to describe the profile of vitamin D serum levels, especially in elderly women with knee osteoarthritis in South Tangerang City, in 2020. Method: This study used a cross-sectional design from the secondary dataof female patients aged over 60 years who had been diagnosed with knee osteoarthritis with a total sample of 110. The sample was selected using consecutive sampling and analyzed using univariate analysis. Results: This study found that 80% of the elderly with knee osteoarthritis have low level vitamin D serum, with 63% had insufficient level, and 17% were deficient. Conclusion: Most of the elderly women with knee osteoarthritis in South Tangerang in 2020 had a low level of vitamin D serum <50 nmol/L.